La tolerancia del infiel. Sobre la relación entre monoteísmo y derechos humanos - Streck, Bernhard (Revista de Antropología Social, 2010)
The Human Rights could not arise on the ground of expanding book religions, because these accept others or non–believers only after their conversion. Only if belief itself has become indifferent it looses its threatening and blasphemy. In the secularized western countries this stadium seems to be reached. In all other world regions the belief has conserved much of its . obligation or has even grown in it. Therefore the Human Rights find bad conditions outside the modern world, and even inside the believers among the immigrants question the newly established tolerance or challenge a new fundamentalism. The messianic movements studied by Riesebrodt, Kepel and others are the main danger for the modern societies and their idea of general human rights.
Keywords: Book religions; Ethical monotheism; Secularization; Human Rights; Messianic movements; Fundamentalism